(Induced) Forgetting to form a collective memory. (July 2014) - Stone, Charles B; Hirst, William
How communities forge collective memories has been a topic of long-standing interest among social scientists and, more recently, psychologists. However, researchers have typically focused on how what is overtly remembered becomes collectively remembered. Recently, though, Stone and colleagues have delineated different types of silence and their influence on how individuals and groups remember the past, what they termed, mnemonic silence. Here we focus on the importance of relatedness in understanding the mnemonic consequences of public silence. We begin by describing two common means of investigating collective memories: the social construction approach and the psychological approach. We subsequently discuss in detail a psychological paradigm, retrieval-induced forgetting, and demonstrate how this initially individual memory paradigm can and has been extended to social contexts in the form of public silence and may provide insights into larger sociological phenomenon, in our case, collective memories. We conclude by discussing avenues of future research and the benefits of including a psychological perspective in the field of collective memory.